The Weight of Bariatric Surgery: Wernicke–Korsakoff Syndrome after Vertical Sleeve Gastrectomy - A Case Series (2024)
In this case series, the simultaneous occurrence of Wernicke’s encephalopathy (WE) and dry beriberi was reported in three patients who underwent vertical sleeve gastrectomy (VSG) between May 2021 and May 2023. All patients were obese women who underwent vertical sleeve gastrectomy (VSG) without immediate postoperative complications, but two weeks later, hyperemesis and subsequent encephalopathy with ocular movement abnormalities and weakness were observed over the following thirty days. Patients were referred to neurology, where due to the high suspicion of WE, thiamine replacement therapy was initiated; meanwhile, diagnostic neuroimaging and blood tests were conducted. Neurological and psychiatric evaluations and neuroconduction studies were performed to assess the clinical evolution and present sequelae. One year after diagnosis, all patients exhibited affective and behavioral sequelae, anterograde memory impairment, and executive functioning deficits. Two patients met the criteria for Korsakoff syndrome. Additionally, peripheral nervous system sequelae were observed, with all patients presenting with sensorimotor polyneuropathy. In conclusion, Wernicke’s encephalopathy requires a high diagnostic suspicion for timely intervention and prevention of irreversible sequelae, which can be devastating. Therefore, raising awareness among medical professionals regarding the significance of this disease is essential.